Mitochondrial complex activity in permeabilised cells of chronic fatigue syndrome patients using two cell types - Cara Tomas; Audrey E. Brown; Julia L. Newton; Joanna L. Elson (PeerJ, 2019)
Abnormalities in mitochondrial function have previously been shown in chronic fatigue syndrome (CFS) patients, implying that mitochondrial dysfunction may contribute to the pathogenesis of disease. This study builds on previous work showing that mitochondrial respiratory parameters are impaired in whole cells from CFS patients by investigating the activity of individual mitochondrial respiratory chain complexes. Two different cell types were used in these studies in order to assess individual complex activity locally in the skeletal muscle (myotubes) (n = 6) and systemically (peripheral blood mononuclear cells (PBMCs)) (control n = 6; CFS n = 13). Complex I, II and IV activity and respiratory activitysupported by fatty acid oxidation and glutaminolysis were measured usingextracellular flux analysis. Cells were permeabilised and combinations of substrates and inhibitors were added throughout the assays to allow states of mitochondrial respiration to be calculated and the activity of specific aspects of respiratory activity to be measured. Results showed there to be no significant differences in individual mitochondrial complex activity or respiratory activity supported by fatty acid oxidation or glutaminolysis between healthy control and CFS cohorts in either skeletal muscle (p ≥ 0.190) or PBMCs (p ≥ 0.065). This is the first study to use extracellular flux analysisto investigate individual mitochondrial complex activity in permeabilised cells in the context of CFS. The lack of difference in complex activity in CFS PBMCs suggests that the previously observed mitochondrial dysfunction in whole PBMCs is due to causes upstream of the mitochondrial respiratory chain.